The Functions of Prospection – Variations in Health and Disease - Bulley, Adam; Irish, Muireann (Frontiers in Psychology, 2018)
Much of human life revolves around anticipating and planning for the future. It has become increasingly clear that this capacity for prospective cognition is a core adaptive function of the mind. Here, we review the role of prospection in two key functional domains: goal-directed behaviour and flexible decision-making. We then survey and categorize variations in prospection, with a particular focus on functional impact in clinical psychological conditions and neurological disorders. Finally, we suggest avenues for future research into the functions of prospection and the manner in which these functions can shift towards maladaptive outcomes. In doing so, we will consider the conceptualisation and measurement of prospection, as well as novel approaches to its augmentation in healthy people and managing its alterations in a clinical context.